Crowdsourcing sugammadex adverse event rates using an in-app survey: feasibility assessment from an observational study. (July 2018) - Jabaley, Craig S.; Wolf, Francis A.; Lynde, Grant C.; O'Reilly-Shah, Vikas N.
Background: Mobile applications (apps) have become a ubiquitous source of clinical decision support. We sought to ascertain the feasibility of using an app platform to obtain a crowdsourced measure of adverse drug reaction reporting rates associated with sugammadex administration and compare it with traditionally-derived estimates. Methods: Using the widely-distributed anesthesia calculator app, 'Anesthesiologist', we surveyed anesthesia providers regarding their experience with adverse drug reactions associated with sugammadex administration. Results: Data were analyzed from 2770 participants in 119 countries responding between March 2016 and May 2017, who were estimated to have administered between 1.6–2.9 million doses (588–1040 administrations per participant). A low and high-end reporting rate of adverse events was estimated based on respondents' reported frequency and duration of sugammadex use. The estimated reporting rate of anaphylaxis due to sugammadex was 0.0055–0.098%, similar in range to previously published estimates. Conclusions: Use of an in-app survey facilitated a global assessment of anesthesia providers and could have useful applications in monitoring adverse events and estimating their rates. Further work is needed to validate this approach for other medications and clinical domains.